The Levels of Financial Literacy in Kampala, Uganda: A comparative analysis using objective and subjective measures : Financial Literacy in Kampala, Uganda - Agabalinda, Colin; Isoh, Alain Vilard Ndi (International Journal of Scientific Research and Management (IJSRM), 2020)
The study presents a comparative analysis of objectively measured and subjectively measured financial literacy in Kampala, Uganda. Financial literacy levels were measured and compared by the demographic characteristics of age, gender, employment status, level of education, and access to financial education. Survey data from a sample of n = 351 adults proportionately selected the five administrative divisions of Kampala in Uganda was analyzed using descriptive statistics, Exploratory Factor Analysis (EFA), and the Analysis of Variance (ANOVA). The findings reveal a high level of self-assessed financial literacy and a low level of objectively measured financial literacy among respondents. On the overall, respondents have a limited understanding of basic concepts of interest rate, inflation, and securities, thus suggesting overestimated levels of financial literacy among people in Kampala. The study finds the overestimation problem more prominent among younger people, and those employed in the formal sector. Further, financial literacy (both objectively and subjectively measured) is higher among men than women; and also higher among the respondents that have had prior financial education. Our findings have vital implications for policy and practice: First, is that financial education is a useful tool in promoting financial literacy. Second, financial education programs in Uganda need to proactively target women, persons aged 35 yrs and above, and self-employed persons operating in the informal sector. Third, there is an urgent need for financial educators to promote awareness on the need for financial education, especially among segments with overestimated levels of financial literacy.